Anti-freezing pervious concrete prepared from recycled aggregate and application of anti-freezing pervious concrete
By using recycled concrete aggregates and nano-silica materials, the proportion design is optimized, and the shortcomings of permeable concrete in terms of strength, frost resistance and durability are solved, efficient resource reuse and performance improvement are achieved, and are suitable for road construction in cold areas.
Patent Information
- Application Number
- CN202510148656.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-15
AI Technical Summary
Existing water-permeable concrete has shortcomings in material and structural properties, especially in terms of strength, frost resistance and durability, which are difficult to meet the needs of cold areas and long-term use.
By completely using recycled concrete aggregates and combining the synergistic effects of nanosilicon dioxide and fly ash, the proportional design is optimized to improve the water permeability, strength and frost resistance of concrete.
It has achieved 100% reuse of waste concrete, significantly reduced resource consumption, improved the water permeability, strength, frost resistance and durability of concrete, and is suitable for low-strength pavement construction in cold areas.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete materials, and in particular relates to antifreeze permeable concrete prepared from recycled aggregate and application thereof. Background Art
[0002] As a new type of environmentally friendly building material, permeable concrete can effectively infiltrate rainwater into the ground through its special pore structure, reduce surface runoff, and improve the urban hydrological environment. It has become the preferred material for low-strength pavements such as urban sidewalks and parking lots, and has gradually gained favor in urban planning and road construction in various places. However, there are still some problems that need to be solved in existing permeable concrete, especially in terms of material and structural performance. Traditional permeable concrete often uses natural sand and gravel as aggregate, which not only consumes a large amount of natural resources, but also with the increasingly stringent environmental protection policies, the supply of natural aggregates has become increasingly tight, and the sustainable use of resources faces challenges.
[0003] As a recycled product of waste concrete, recycled concrete aggregate has good resource recovery potential. Using recycled concrete aggregate to prepare permeable concrete can not only effectively reduce the accumulation of construction waste and reduce resource consumption, but also significantly reduce the production cost of permeable concrete. However, permeable concrete prepared with recycled concrete aggregate has problems such as low strength, poor frost resistance, and easy clogging, which directly affects the performance of recycled permeable concrete in cold areas and long-term use. In order to improve the durability and stability of permeable concrete, it is necessary to optimize the mix design and material selection. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a frost-resistant permeable concrete prepared with recycled aggregate and its application. The concrete of the present invention fully uses recycled concrete aggregates, realizes the recycling and reuse of waste concrete, reduces the use of natural sand and gravel, significantly reduces resource consumption, and combines the synergistic effect of nano-silicon dioxide and fly ash to optimize the mix design and improve the permeability, strength and frost resistance of concrete.
[0005] In order to achieve the above technical objectives, the technical solution adopted by the embodiment of the present invention is: In a first aspect, an embodiment of the present invention provides a frost-resistant permeable concrete prepared from recycled aggregate, comprising the following components by weight: 60-90 parts of cement, 10-40 parts of mineral admixtures, 0.5-1 parts of nano-silicon dioxide, 250-350 parts of aggregates and 28-35 parts of water, wherein the mineral admixtures are added at a cement replacement rate of 10%-40%, and the amount of nano-silicon dioxide added is 0.5%-1% of the total mass of cement and mineral admixtures; The aggregate includes coarse aggregate and fine aggregate, wherein the mass proportion of the coarse aggregate is 70%-85%, and the mass proportion of the fine aggregate is 15%-30%; The coarse aggregate is recycled concrete aggregate, and the fine aggregate is recycled concrete machine-made sand; The porosity of the permeable concrete is 18%-24%.
[0006] The above-mentioned proportion can achieve the synergistic effect of recycled concrete machine-made sand, fly ash and nano-silicon dioxide, significantly improving the strength, frost resistance and durability of permeable concrete.
[0007] Among them, permeable concrete uses recycled concrete aggregate instead of natural coarse aggregate, and recycled concrete machine-made sand instead of natural river sand, achieving 100% recycling of waste concrete.
[0008] Furthermore, the technical indicators of the recycled concrete aggregate are: The particle size is 4.75-16mm, with appropriate particle size distribution; The crushing value is not more than 30% to ensure that the aggregate has sufficient strength to support the use of permeable concrete; The mud content is controlled below 1% to ensure the cleanliness of the aggregate and not affect the strength and permeability of the concrete; The water absorption rate is controlled below 8% to prevent the recycled aggregate from absorbing excessive water and affecting the performance of the concrete.
[0009] Furthermore, the technical indicators of the recycled concrete machine-made sand are: The particle size distribution is 0-4.75mm, with appropriate particle gradation; The mud content shall not exceed 3% and the water absorption rate shall not exceed 10%; The pH value should be controlled between 6 and 8 to avoid excessively high pH values that may affect the durability of concrete; The particle shape is quasi-round or round, with a smooth surface; It does not contain heavy metals including lead, cadmium and arsenic, avoiding pollution to the environment.
[0010] The particle size distribution of recycled concrete aggregate has been optimized, and the ratio of coarse aggregate (4.75mm-16mm) to fine aggregate (0-4.75mm) is coordinated to ensure the existence of a continuous pore structure in the permeable concrete. The void ratio of the permeable concrete is controlled by adjusting the ratio of coarse and fine aggregates. The void ratio is 18%-24%, which effectively improves the drainage performance and reduces the decrease in permeability caused by fine particles clogging the pores during long-term use.
[0011] Furthermore, the mineral admixture includes one or more of fly ash, silica fume, slag powder and steel slag powder. The amount of addition is determined according to the design grade of concrete. The active ingredients react with cement to form more CSH gel, which improves the compactness of concrete and significantly enhances the frost resistance of concrete. It is especially suitable for freeze-thaw cycle conditions in low temperature environments such as the north, and reduces the construction cost.
[0012] Furthermore, the freeze-thaw cycle test results of the permeable concrete show that in a freeze-thaw cycle environment of -20°C, the compressive strength loss of the concrete after 10 freeze-thaw cycles does not exceed 15%, and the volume expansion does not exceed 2%, which meets the anti-freeze standards used in cold regions such as the north.
[0013] Furthermore, the water-cement ratio of the permeable concrete is 0.28-0.35.
[0014] In the second aspect, an embodiment of the present invention provides an application of frost-resistant permeable concrete prepared with the recycled aggregate described in the first aspect, wherein the permeable concrete is used for the construction of urban slow-moving systems including municipal sidewalks, bicycle lanes, river landscape roads and community roads.
[0015] Furthermore, the method for constructing an urban slow-moving system by permeable concrete construction comprises the following steps: (1) Mix the recycled concrete aggregate and recycled concrete machine-made sand according to the proportion, add cement, mineral admixtures, nano-silicon dioxide and water, and stir evenly; (2) spreading the mixture obtained in step (1) on the construction site and vibrating and compacting it; (3) Keep it moist during curing to ensure that the concrete is fully hydrated.
[0016] Furthermore, the paving thickness in step (2) is 80-120 mm.
[0017] The technical solution provided by the embodiment of the present invention has the following beneficial effects: (1) The frost-resistant permeable concrete of the present invention fully uses recycled concrete aggregates, realizes the recycling and reuse of waste concrete, reduces the use of natural sand and gravel, and significantly reduces resource consumption. At the same time, the addition of mineral admixtures and nano-silicon dioxide improves the performance of concrete, has significant environmental friendliness, economy and performance advantages, and is suitable for various types of urban greening, sidewalks, parking lots and other low-strength and high-permeability road construction.
[0018] (2) The frost-resistant permeable concrete of the present invention has excellent water permeability, high strength, excellent frost resistance and durability. The optimized particle size grading and porosity design keep the water permeability of the concrete above 90-110 mL / s, which is far superior to the performance of traditional permeable concrete. The addition of mineral admixtures and nano-silica significantly improves the frost resistance. The strength loss rate of the concrete after freeze-thaw cycles is less than 15%. It is suitable for low-strength pavements such as sidewalks and parking lots in cold areas. Its freeze-thaw performance is far superior to that of traditional permeable concrete, and it can maintain stable structural performance during freeze-thaw cycles.
[0019] (3) The mineral admixture in the frost-resistant permeable concrete of the present invention forms more calcium silicate hydrate CSH gel through active reaction, which significantly improves the compactness and durability of the concrete; The frost-resistant permeable concrete of the present invention effectively reduces the formation of microcracks by means of the nano-effect of nano-silicon dioxide, eliminates harmful pores in the concrete, and reduces water retention, thereby improving the frost resistance, impermeability and durability of the concrete; The mineral admixtures, nano-silica and active ingredients in recycled concrete machine-made sand further play a secondary hydration role, further improving the mechanical properties of concrete and reducing cement consumption.
[0020] (4) The frost-resistant permeable concrete of the present invention is suitable for urban slow-moving systems, such as municipal sidewalks, bicycle lanes, river landscape roads, community roads, etc., especially for road projects with high requirements for sponge city systems and low strength requirements, as well as permeable pavement construction in cold regions with high requirements for antifreeze performance. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0022] Example 1 A frost-resistant permeable concrete prepared with recycled aggregate has a designed cement content of 400 kg / m³. The actual components of the cement include: 280 kg / m³ cement and 120 kg / m³ mineral admixture (specifically fly ash) (cement replacement rate is 30%), 2.8 kg / m³ nano-silicon dioxide, 1200 kg / m³ aggregate and 120 kg / m³ water.
[0023] Aggregates include coarse aggregate and fine aggregate, totaling 1200 kg / m³, of which the mass proportion of coarse aggregate is 75%, i.e., 900 kg / m³ of coarse aggregate, and the mass proportion of fine aggregate is 25%, i.e., 300 kg / m³ of fine aggregate; the coarse aggregate is recycled concrete aggregate, and the fine aggregate is recycled concrete machine-made sand; The technical indicators of recycled concrete aggregate are: particle size 4.75-16mm (4.75mm≤d≤16mm), crushing value 28.5%, water absorption rate 6.7%, and mud content 0.6%.
[0024] The technical indicators of recycled concrete machine-made sand are: particle size 0-4.75mm (0<d<4.75mm), water absorption rate 8.8%, pH value 7.5, and mud content 2.4%.
[0025] Fly ash: Use activated fly ash that meets the current standard of "Fly ash used in cement and concrete" (GB / T 1596). It has fine particle size and large specific surface area, can produce a good hydration reaction with cement, and improve the density and frost resistance of concrete.
[0026] Nano-silica: Selecting nano-silica with a particle size of 10-20nm can effectively enhance the frost resistance, impermeability and crack resistance of concrete through its nano effect.
[0027] The method for forming a sidewalk with permeable concrete comprises the following steps: (1) Mixing and stirring Dry material mixing: First, evenly mix the coarse aggregate, fine aggregate, mineral admixture, nano-silica and cement to ensure that all materials are fully dispersed in the dry mixing state.
[0028] Wet mixing process: Then add appropriate amount of water according to the water-cement ratio of 0.30 and continue mixing for 5 to 7 minutes to ensure that all dry materials are fully moistened and mixed evenly.
[0029] In order to ensure the uniformity of concrete, an efficient mixer should be used to avoid long-term standing resulting in stratification of the mixture; during the mixing process of concrete, the mixing time and the amount of water added must be strictly controlled; excessive mixing or excessive water may cause the aggregate and cement slurry to separate, leading to segregation problems.
[0030] (2) Construction process Spreading: Spread the mixed permeable concrete evenly on the construction ground with a thickness of 120mm.
[0031] Vibration compaction: Use a vibrator to compact the concrete after paving. The vibration time should be controlled within 2 minutes to avoid aggregate segregation caused by excessive vibration. The frequency and amplitude of the vibrator should be precisely controlled to ensure uniform distribution of coarse and fine aggregates. The frequency of the vibrator should be controlled at 2000 times / minute and the amplitude should be within 4mm.
[0032] Surface finishing: After paving, the surface should be lightly trimmed to make it flat and without obvious bumps, to ensure unobstructed surface pores and ensure water permeability.
[0033] (3) Maintenance After concrete is spread, wet curing should be carried out for at least 7 days to ensure sufficient hydration. Keeping the surface moist during curing can effectively improve the hydration reaction of cement and fly ash, and enhance the density and frost resistance of concrete.
[0034] After 28 days of curing, the core was taken and its performance was measured in the laboratory. The test results are as follows: compressive strength 17.8MPa; flexural strength 2.62MPa; effective porosity: 20.4%; water permeability coefficient: 3.21mm / s. The measurement results show that the four key performance indicators of recycled aggregate permeable concrete meet the requirements.
[0035] Example 2 A frost-resistant permeable concrete prepared with recycled aggregate has a designed cement content of 500 kg / m³. The actual components of the cement include: 400 kg / m³ of cement and 100 kg / m³ of mineral admixtures (specifically fly ash and steel slag powder, with a mass ratio of 1:1) (cement replacement rate is 20%), 5 kg / m³ of nano-silicon dioxide, 1300 kg / m³ of aggregate, and 175 kg / m³ of water.
[0036] Aggregates include coarse aggregate and fine aggregate, of which coarse aggregate is 1000 kg / m³ and fine aggregate is 300 kg / m³; The coarse aggregate is recycled concrete aggregate, and the fine aggregate is recycled concrete machine-made sand.
[0037] The technical indicators of recycled concrete aggregate are: The particle size is 4.75-16mm (4.75mm≤d≤16mm), the crushing value is 26%, the mud content is 0.8%, and the water absorption rate is 6.0%.
[0038] The technical indicators of recycled concrete machine-made sand are: The particle size distribution is 0-4.75mm (0<d≤4.75mm), the mud content is 2.1%, and the water absorption rate is 9.4%; the pH value is 7.4, the particle shape is quasi-round or round, and the surface is smooth; it does not contain heavy metals including lead, cadmium, and arsenic.
[0039] Fly ash: Use activated fly ash that meets the current standard of "Fly ash used in cement and concrete" (GB / T 1596). It has fine particle size and large specific surface area, can produce a good hydration reaction with cement, and improve the density and frost resistance of concrete.
[0040] Nano-silica: Selecting nano-silica with a particle size of 10-20nm can effectively enhance the frost resistance, impermeability and crack resistance of concrete through its nano effect.
[0041] The above-mentioned method for constructing urban roads and parking lots with permeable concrete comprises the following steps: (1) Pretreatment of recycled aggregate: Recycled aggregate has irregular particle shape and possible impurities. Before construction, it is necessary to screen the recycled aggregate to remove harmful impurities (such as oil, soil, etc.) and ensure that the particle size distribution meets the design requirements (generally a particle size range of 5-20 mm is used); (2) Base preparation: Before construction, first clean the foundation surface to ensure that the ground is flat, clean and free of debris. According to the design requirements, set up a drainage system to ensure that the construction area has good drainage conditions.
[0042] (3) Concrete preparation: According to the designed formula, accurately weigh cement, mineral admixtures, nano-silica, coarse aggregate, fine aggregate and water, mix them in proportion, and stir them evenly using a mixer; (4) Casting construction: When casting recycled aggregate permeable concrete, it should be roughly leveled manually first, and then fine-finished using a friction leveler to ensure that the concrete surface is flat and dense.
[0043] (5) Surface leveling: After pouring, first use a scraper to level the control edges on both sides, then use a vibrating roller to vibrate and compact to ensure that the surface is flat and tight. The vibrating position of the vibrator should be evenly arranged to avoid uneven vibration. Finally, use a level or a wooden board to level the surface to keep it flat and smooth to avoid excessive friction that affects the water permeability.
[0044] (6) Maintenance: After construction is completed, carry out moisturizing maintenance and cover with wet cloth to keep the surface moist to prevent cracking.
[0045] (7) Quality inspection: After the construction is completed, the permeable concrete needs to be tested for compressive strength, permeability and other performance tests to ensure that it meets the design requirements.
[0046] After curing for 28 days, the core was taken and its performance was measured in the laboratory. The test results are as follows: compressive strength 20.2MPa; flexural strength 2.51MPa; effective porosity: 18.7%; water permeability coefficient: 2.44mm / s. The measurement results show that the four key performance indicators of recycled aggregate permeable concrete meet the requirements.
[0047] Comparative Example The comparative example uses conventional concrete, which includes the following components: Cement: 500 kg / m³; Natural gravel: 1000 kg / m³; Natural sand: 400 kg / m³; Water: 180 kg / m³.
[0048] The frost-resistant permeable concrete prepared from recycled aggregate in Example 2 of the present invention comprises the following components: Cement: 400 kg / m³; Mineral admixture: 100 kg / m³, specifically fly ash and steel slag powder, the ratio of the two is 1:1; Recycled coarse aggregate: 1000kg / m³; Regenerated machine-made sand: 300 kg / m³; Nano silicon dioxide 1% (calculated based on the total mass of cement and mineral admixtures): 5 kg / m³; Water: 175 kg / m³.
[0049] The performance of the conventional concrete in the comparative example and the recycled aggregate permeable concrete in Example 2 was compared mainly in terms of mechanical properties, water permeability, frost resistance and economy: Mechanical properties The 28d compressive strength of conventional concrete is 24.4 MPa, and the compressive strength of recycled aggregate permeable concrete in Example 2 of the present invention is 20.2 MPa. Although the compressive strength of recycled aggregate permeable concrete is slightly lower than that of conventional concrete, it still meets the use requirements of permeable concrete and has good construction performance.
[0050] Water Permeability The water permeability coefficient of conventional concrete is 1.83 mm / s, and the water permeability coefficient of the recycled aggregate permeable concrete of Example 2 of the present invention is 2.44 mm / s. The water permeability of the recycled aggregate permeable concrete is significantly better than that of conventional concrete, showing its excellent performance in rainwater permeability.
[0051] Frost resistance The frost-resistant permeable concrete of Example 2 of the present invention performs well in frost resistance, with a mass loss rate of 2.33%, a compressive strength loss rate of 14.49%, and a flexural strength loss rate of 25.93% after 50 freeze-thaw cycles, while the corresponding loss rates of the conventional formula concrete in the comparative example are 4.69%, 18.06%, and 28.57%, respectively. This shows that the synergistic effect of mineral admixtures and nano-silica enhances the interfacial adhesion of permeable concrete, and after freeze-thaw cycles, the durability of recycled aggregate permeable concrete is basically guaranteed, which is suitable for application in cold regions.
[0052] The strength of the permeable concrete in Example 2 is slightly lower than that of the concrete with conventional formula, but the strength reduction does not exceed 20% and meets the requirements of the specification, while the frost resistance and permeability are improved by 10%.
[0053] Economical Permeable concrete made from recycled aggregates reduces the cost per cubic meter by about 30% compared to conventional concrete. Recycled aggregates are widely available and relatively cheap, making them economical and suitable for promotion and application in large-scale urban sidewalk and road projects.
[0054] The present invention innovatively combines recycled concrete machine-made sand, mineral admixtures and nano-silica. Through the synergistic effect of the three, it not only achieves 100% recycling of waste concrete, but also effectively improves the frost resistance, impermeability and mechanical properties of concrete, providing a new technical path for the widespread application of permeable concrete.
[0055] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A frost-resistant permeable concrete prepared from recycled aggregate, characterized in that: The following components are included by weight: 60-90 parts of cement, 10-40 parts of mineral admixtures, 0.5-1 parts of nano-silicon dioxide, 250-350 parts of aggregates and 28-35 parts of water, wherein the mineral admixtures are added at a cement replacement rate of 10%-40%, and the amount of nano-silicon dioxide added is 0.5%-1% of the total weight of cement and mineral admixtures; The aggregate includes coarse aggregate and fine aggregate, wherein the mass proportion of the coarse aggregate is 70%-85%, and the mass proportion of the fine aggregate is 15%-30%; The coarse aggregate is recycled concrete aggregate, and the fine aggregate is recycled concrete machine-made sand; The porosity of the permeable concrete is 18%-24%.
2. The frost-resistant permeable concrete prepared from recycled aggregate according to claim 1, characterized in that: The technical indicators of the recycled concrete aggregate are: The particle size is 4.75-16mm, the crushing value is not more than 30%, the mud content is controlled below 1%, and the water absorption rate is controlled below 8%.
3. The frost-resistant permeable concrete prepared from recycled aggregate according to claim 1, characterized in that: The technical indicators of the recycled concrete machine-made sand are: The particle size distribution is 0-4.75mm, the mud content does not exceed 3%, and the water absorption rate does not exceed 10%; The pH value is controlled between 6-8, the particle shape is quasi-spherical or round, and the surface is smooth; it does not contain heavy metals including lead, cadmium, and arsenic.
4. The frost-resistant permeable concrete prepared from recycled aggregate according to claim 1, characterized in that: The mineral admixture includes one or more of fly ash, silica ash, slag powder and steel slag powder.
5. The frost-resistant permeable concrete prepared from recycled aggregate according to claim 1, characterized in that: The freeze-thaw cycle test results of the permeable concrete are as follows: in a freeze-thaw cycle environment at -20°C, the compressive strength loss of the concrete after 10 freeze-thaw cycles does not exceed 15%, and the volume expansion does not exceed 2%.
6. The frost-resistant permeable concrete prepared from recycled aggregate according to claim 1, characterized in that: The water-cement ratio of the permeable concrete is 0.28-0.
35.
7. Application of frost-resistant permeable concrete prepared from recycled aggregate according to any one of claims 1 to 6, characterized in that: The permeable concrete is used for the construction of urban slow-moving systems including municipal sidewalks, bicycle lanes, river landscape roads and community roads.
8. The use of the frost-resistant permeable concrete prepared from recycled aggregate according to claim 7, characterized in that: The method for forming an urban slow-moving system through construction of permeable concrete comprises the following steps: (1) Mix the recycled concrete aggregate and recycled concrete machine-made sand according to the proportion, add cement, mineral admixtures, nano-silicon dioxide and water, and stir evenly; (2) spreading the mixture obtained in step (1) on the construction site and vibrating and compacting it; (3) Keep it moist during curing to ensure that the concrete is fully hydrated.
9. The use of the frost-resistant permeable concrete prepared from recycled aggregate according to claim 8, characterized in that: The paving thickness in step (2) is 80-120 mm.